Data from: Comparative population genomics reveals key barriers to dispersal in Southern Ocean penguins - Clucas, Gemma V.; Younger, Jane L.; Kao, Damian; Emmerson, Louise; Southwell, Colin; Wienecke, Barbara; Rogers, Alex D.; Bost, Charles-Andre; Miller, Gary D.; Polito, Michael J.; Lelliot, Patrick; Handley, Jonathan; et al. (Zenodo, 2018)
The mechanisms that determine patterns of species dispersal are important factors in the production and maintenance of biodiversity. Understanding these mechanisms helps to forecast the responses of species to environmental change. Here we used a comparative framework and genome-wide data obtained through RAD-seq to compare the patterns of connectivity among breeding colonies for five penguin species with shared ancestry, overlapping distributions, and differing ecological niches, allowing an examination of the intrinsic and extrinsic barriers governing dispersal patterns. Our findings show that at-sea range and oceanography underlie patterns of dispersal in these penguins. The pelagic niche of emperor (Aptenodytes forsteri), king (A. patagonicus), Adélie (Pygoscelis adeliae) and chinstrap (P. antarctica) penguins facilitates gene flow over thousands of kilometres. In contrast, the coastal niche of gentoo penguins (P. papua) limits dispersal, resulting in population divergences. Oceanographic fronts also act as dispersal barriers to some extent. We recommend that forecasts of extinction risk incorporate dispersal and that management units are defined by at-sea range and oceanography in species lacking genetic data. Adelie penguins - VCF of SNP dataset Adelie.vcf Chinstrap penguins - VCF of SNP dataset Chinstrap.vcf Gentoo penguins - VCF of full SNP dataset includes outlier loci Gentoos_all-SNPs.vcf Gentoo penguins - VCF of neutral SNP dataset outlier loci removed Gentoos_neutral-SNPs.vcf Gentoo penguins - nexus file for BFD* Input file of SNPs for BFD* species delimitation Gentoos_input_for_BFD.nex Gentoo penguins - phylip file for RAxML Phylip alignment of SNPs for phylogenetic inference in RAxML Gentoos_input_for_RAxML.phy Gentoos_input_for_SNAPP_set1 XML input file for SNAPP analysis of gentoo penguins - set 1 Gentoos_input_for_SNAPP_set2 XML input file for SNAPP analysis - set 2